Antibiofilm effect and mechanism of protocatechuic aldehyde against Vibrio parahaemolyticus - Liu, Yawen; Wang, Li (Frontiers in Microbiology, 2022)
This study investigated the effect of protocatechuic aldehyde (PCA) on Vibrio parahaemolyticus biofilm formation and its effects on gene expression. Crystal violet assay, metabolic activity assay, and fluorescence experiments were used to evaluate the antibiofilm activities of PCA and to reveal its possible antibiofilm mechanisms using transcriptomic analysis. The results indicated that the minimum antibacterial concentration of PCA against V. parahaemolyticus was 300 µg/mL. PCA (9.375 µg/mL) inhibited biofilm generation and adhesion of the mature biofilm. PCA (75 µg/mL) significantly reduced the metabolic viability of V. parahaemolyticus, reduced polysaccharide production, and inhibited cell surface flagella-mediated swimming and aggregation phenotypes. Meanwhile, transcriptome analysis showed that the key genes of V. parahaemolyticus expressed under PCA (75 µg/mL) inhibition were mainly related to biofilm formation (pfkA, galE, narL, and oppA), polysaccharide production and adhesion (IF, fbpA, and yxeM), and motility (cheY, flrC, and fliA). By regulating these key genes, PCA reduced biofilm formation, suppressed polysaccharide production and transport, and prevented the adhesion of V. parahaemolyticus, thereby reducing the virulence of V. parahaemolyticus. This study demonstrated that protocatechuic aldehyde can be used to control V. parahaemolyticus biofilm to ensure food safety.